Current Perspectives of Prenatal Sonography of Umbilical Cord Morphology - Sherer DM; Al-Haddad S; Cheng R; Dalloul M (Dove Medical Press, 2021)
David M Sherer, Sara Al-Haddad, Regina Cheng, Mudar Dalloul The Division of Maternal Fetal Medicine, The Department of Obstetrics and Gynecology, State University of New York (SUNY), Downstate Health Sciences University, Brooklyn, NY, USACorrespondence: David M ShererDivision of Maternal-Fetal Medicine, Department of Obstetrics and Gynecology, State University of New York (SUNY), Downstate Health Sciences University, 450 Clarkson Avenue, Box 24, Brooklyn, NY, USATel +1 718 270-2081Fax +1 718 270-4122Email davidmsherer@gmail.comAbstract: The umbilical cord constitutes a continuation of the fetal cardiovascular system anatomically bridging between the placenta and the fetus. This structure, critical in human development, enables mobility of the developing fetus within the gestational sac in contrast to the placenta, which is anchored to the uterine wall. The umbilical cord is protected by unique, robust anatomical features, which include: length of the umbilical cord, Wharton's jelly, two umbilical arteries, coiling, and suspension in amniotic fluid. These features all contribute to protect and buffer this essential structure from potential detrimental twisting, shearing, torsion, and compression forces throughout gestation, and specifically during labor and delivery. The arterial components of the umbilical cord are further protected by the presence of Hyrtl's anastomosis between the two respective umbilical arteries. Abnormalities of the umbilical cord are uncommon yet include excessively long or short cords, hyper or hypocoiling, cysts, single umbilical artery, supernumerary vessels, rarely an absent umbilical cord, stricture, furcate and velamentous insertions (including vasa previa), umbilical vein and arterial thrombosis, umbilical artery aneurysm, hematomas, and tumors (including hemangioma angiomyxoma and teratoma). This commentary will address current perspectives of prenatal sonography of the umbilical cord, including structural anomalies and the potential impact of future imaging technologies.Keywords: prenatal ultrasound, umbilical cord, color Doppler imaging